2017
DOI: 10.1016/j.bandc.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Objects rapidly prime the motor system when located near the dominant hand

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractObjects are said to automatically "afford" various actions depending upon the motor repertoire of the actor. Such affordances play a part in how we prepare to handle or manipulate tools and other objects. Evidence obtained through fMRI, EEG and TMS has proven that this is the case but, as yet, the temporal evolution of affordances has not been fully investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 31 publications
4
18
4
Order By: Relevance
“…Contrary to these lines of evidence, Rowe et al. (2017) failed to find amplitude differences in the posterior N1 when comparing graspable objects to an empty desk.…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…Contrary to these lines of evidence, Rowe et al. (2017) failed to find amplitude differences in the posterior N1 when comparing graspable objects to an empty desk.…”
Section: Discussioncontrasting
confidence: 95%
“…In the present study, we showed that an elongated wooden object, ambiguous in size and function, is processed differently depending on the context previously established by conceptual priming. When the pencil context, and thus a context of graspable objects, was primed, the target triggered larger posterior P1 amplitudes, indicative of increased visual attention, as well as a reduced posterior N1 and an enhanced frontal negativity, which has been previously related to object affordance ( Proverbio et al., 2011 ; Rowe et al., 2017 ). Activation of certain brain areas was also stronger.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations